Relational schemas as mediators of innovative moments in symptom improvement in major depression - Batista, João (2017)
Objectives: Innovative moments (IMs) are exceptions to the maladaptive framework of meaning that typically motivates clients to seek psychotherapy, and previous studies have shown that IMs are associated with psychotherapy outcomes. While IMs are exceptions that occur at the level of the therapeutic conversation, relational schemas are more stable patterns, and their increased flexibility may facilitate change during psychotherapy. With this in mind, we tested the hypothesis that IMs contribute to outcomes by improving the flexibility of relational schemas. Method: The Core Conflictual Relationship Theme (CCRT) was used to assess relational schemas. IMs were evaluated using the Innovative Moments Coding System. The sample included 22 clients diagnosed with major depressive disorder. The flexibility of the three components of the CCRT (Wishes, responses of the self (RS), and responses of others (RO)) were tested as mediators between IMs and outcomes. Results: The flexibility of the RS was a mediator between IMs and outcomes, but Wishes and RO were not. Conclusion: These findings align with previous research showing that RS is the component most open to change, whereas the other components seem less sensitive to change during brief therapy.